KONSELING BEHAVIORISTIK DALAM MEMBENTUK PERILAKU MANDIRI MERAWAT DIRI PADA TUNAGRAHITA - Sakinah, Umul (UIN Sunan Kalijaga Yogyakarta, 2018)
Mental retardation as a mental disability that affects the brain's working system intellectually, impaired motor sensors which resulted in limitation in living the life in social environment. This makes it difficult to mental retardation limitation to live independently, especially in taking care of yourself. From the background of the problem, the need for the formation of behavior in an effort to take care of yourself for mental retardation using the behavioristik approach to counseling, specifically using the technique of classical conditioning. The object of this writing is mental retardation along with analysis of the behavioristik counseling who became an settlement approach. The result of this writing recommends the use of behavioristik classical conditong as analysis counselling in helping form a mental retardation behavior of self help in caring for yourself. Kata kunci: Mental retardation, behavioristik counseling, self-sufficiency taking care of yourself